EU:n maatilatypologia Suomessa - Tiainen, Simo; Katajamäki, Esa (Maatalouden taloudellinen tutkimuslaitos, 1996)
This publication presents a description of the Community typology for agricultural holdings and the way how that is applied in Finland. The objective of the Community typology is to achieve a uniform classification of holdings in the European Union. The classification is based on the type of farming and the economic size, which are determined on the basis of standard gross margin. The Community typology for agricultural holding and the statistics where it is applied, the Community Farm Accountancy Data Network and the Community farm structure survey are based to the EU legislation. Joining to the EU in 1995 has meant that the stipulations concerning the typology and its applications entered into force also in Finland. The first half of this publication presents a thorough description of the Community typology as well as its main applications. This part also includes the description of the method of classifying the holdings in parallel statistics in Finland. In the empirical part of the publication the Finnish farms are classified according the Community typology rules. The physical characteristics of the holdings are based on the Rural Business Register. The standard gross margins for each characteristic are calculated for four geografical regions in a way agreed with Eurostat and DG VI. The outcome is the breakdown of Finnish farms by type farming and by economic size based on the Community typology. The first concrete applications of the new typology system in Finland are the determination of the sample needed for the Community Farm Accountancy Data Network and the Community Farm Structure Survey. In the last part of the publication the first sample for FADN in Finland is determined. The Community typology has many benefits in the future in Finland. It will be one important base for international comparations between holdings. It also facilitates for example the development of the calculation the results of Finnish bookkeeping farms. When the same typology is used the results of the bookkeeping farms can be extrapolated to those field of observation.
Keywords: Ma; maatilatypologia; luokittelu; rakennetilastot; EU; Suomi; maatalous; maatilat; kannattavuus; Euroopan unioni; agriculture; farms; classification; accounting; European Union; Finland